PENGARUH PENGGUNAAN MEDIA BUKU CERITA RAKYAT TERHADAP MEMBACA PEMAHAMAN SISWA KELAS III DI SD INPRES BORONGUNTIA KEC. BAJENG KAB. GOWA - Rahma Mutmainna; Andi Adam; Ratnawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This type of research is experimental research (pre-experimental design) with a one-group pretest-posttest design. The subjects in this research were class III students at SD Inpres Boronguntia Kec. Bajeng District. Gowa with a total of 21 students. The sampling technique used is pursive sampling technique, namely a sampling technique. The data collection techniques used in this research were pretest, treatment and posttest. The data analysis techniques used in this research are descriptive statistical analysis techniques and inferential analysis techniques. The results of the research show that the mean (average) value of the pretest is 41 while the mean (average) value of the posttest is 84.76. So it can be concluded that the use of folklore books influences the reading comprehension ability of class III students at SD Inpres Boronguntia, Kec. Bajeng District. Gowa. The results obtained from the t-test on the SPSS application are 11.504, so it can be said that the calculation obtained is 11.504. Next, compare it with the t distribution table, for an error of 5% and d.b = N-2=21-2 =19, the value is 1.72913. The calculated result is greater than ttable so that H0 is rejected and H1 is accepted. The data results show that the use of folklore book media influences the reading comprehension skills of class III students at SD Inpres Boronguntia, Kec. Bajeng District. Gowa .